THE TRADITIONS AND CUSTOMS OF BRITISH PEOPLE IN THEIR FESTIVALS - Rajabova Zuxro; Botirova Hakima (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article is about the culture, traditions and customs of British people. By reading it we can pick up reliable information about the lifestyle of British nation and the roots of their customs